Haemostatic function of dogs naturally envenomed by the African puffadder (Bitis arietans) or snouted cobra (Naja annulifera) - Schoeman, Johan P. (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2012.